SISTEM PENGUPAHAN OUTSOURCING DALAM PERSPEKTIF ISLAM (STUDI KASUS PADA PT. MAHAKAM KENCANA INTAN PADI SURABAYA) - M. Sahirul Alim; Sri Herianingrum (Universitas Airlangga, 2018)
This study aims to analyze the implementation of wage system outsourcing in PT Mahakam Kencana Intan Padi Surabaya in Islamic Perspective. Methods of research for this study used a qualitative approach with case study methods and descriptive analyzes were conducted information about wage system outsourcing in PT Mahakam Kencana Intan Padi Surabaya in depth, observed and validated data by triangulation. The results showed that implementation of oursourcing labor remuneration at PT Mahakam Kencana Intan Padi Surabaya in Islamic Perspective according based Al-Quran and Al-Hadith. The indicators used by the terms of feasibility of minimum wages and equity among workers. Insights justice in Islamic perspective is described comparative labor positions corresponding salaries earned. Payment of salaries in PT Mahakam Kencana Intan Padi accordance timelines. PT Mahakam Kencana Intan Padi is not sharia company but the results of the research conclusion is the wage system in PT Mahakam Kencana Intan Padi according Islamic perspective. REFERENCESAbdurrahman Al-Maliki. 2009. Politik Ekonomi Islam, Bogor: Al-Azhar PressBaqir Syarif Al- Qasyari. 2007.Keringat Buruh,Jakarta: Al-Huda. Hal 159Egi, Sudjana. 2002. Bayarlah Upah Sebelum Keringat Kering, Jakarta: APMI, hal 41.Ibid, Surat At-Taubah ayat 105.Ibid, Surat Yusuf ayat 72.M. A Maman. 1998. Ekonomi Islam Theori dan Praktek, Jakarta.Edisi 5. Halaman 116Muba, Wang. 2010. Tenaga Kerja Outsourcing, Artikel Diakses dari http//wangmuba.com.Pt.mahakamkencanaintanpadi.co.id. di akses 19 Juni 2014Qardhawi (al), Yusuf. Peran Nilai dan Moral dalam Perekonomian Islam. Jakarta: Robbani Press, 2001.Saeful Rahmat, Pupu. 2009. Penelitian Kualitatif,Jakarta: Equilibrium Vol.5 No. 9 Sugiarto, Rudi. 2012. Skripsi S1 jurusan Ekonomi Islam UIN Syarif Hidayatullah. Sistem Pengupahan pada PT Permata Indonesia dalam Ekonomi Islam. Jakarta. Sugiyono. (2012). Metode Penelitian Kualitatif dan R&D. Bandung: Alfabeta.Syam, Zulkhaeril. 2011. Pengupahan Karyawan Dalam Perspektif Fiqih Muamalah (Studi Kasus Pada Home Idustri, konveksi kalibata Jakarta Selatan). Jakarta.Wangsa, Sugianto dan Ming Kuang, Tan. 2011. Penelitian Kualitatif dengan studi kasus. Jakarta.Yin, Robert K. 2010. Studi Kasus: Desain dan Metode, Jakarta. PT. Raja Grafindo Persada